LEGO friends : leveraging competitive advantage - Mazzeo, Michael; Merkley, Greg ([London] : SAGE, 2016)
In December 2011 the Lego Group (TLG) announced the launch of Lego Friends, the company's sixth attempt to market a product to girls. Lego Friends, which was supported by a $40 million global marketing campaign, was designed to introduce the fun of building with Lego bricks to girls, who represented less than 10 percent of Lego's audience. The company's poorly executed brand extensions and move from free-form building sets to story-driven kits had nearly cost it its independence in 2004, so the launch of Lego Friends was strategically important. However, within hours of the product's appearance it was heavily criticized for reinforcing gender stereotypes and damaging the valuable Lego brand. This cae study discusses this topic.
Originally Published in: Mazzeo, M., & Merkley, G. (2012). LEGO Friends: Leveraging Competitive Advantage. 5-312-500. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; LEGO koncernen (Denmark); Brand name products -- Case studies; Branding (Marketing) -- Case studies; LEGO toys -- Case studies; Competition -- Case studies